Single Cell Genomics-Based Analysis of Gene Content and Expression of Prophages in a Diffuse-Flow Deep-Sea Hydrothermal System - Labonté, Jessica M.; Pachiadaki, Maria; Fergusson, Elizabeth; McNichol, Jesse; Grosche, Ashley; Gulmann, Lara K.; Vetriani, Costantino; Sievert, Stefan M.; Stepanauskas, Ramunas (Frontiers in Microbiology, 2019)
Phage-host interactions likely play a major role in the composition and functioning of many microbiomes, yet remain poorly understood. Here we employed single cell genomics to investigate phage–host interactions in a diffuse-flow, low-temperature hydrothermal vent that may be reflective of a broadly distributed biosphere in the subseafloor. We identified putative prophages in 10% of 126 sequenced single amplified genomes (SAGs), with no evidence for lytic infections, which is in stark contrast to findings in the surface ocean. Most were distantly related to known prophages, while their hosts included bacterial phyla Bacteroidetes, Chlorobi, Proteobacteria, Lentisphaerae, Spirochaetes, and Thermotogae. Our results suggest the predominance of lysogeny over lytic interaction in diffuse-flow, deep-sea hydrothermal vents, despite the high productivity of the dominant Campylobacteria (formerly Epsilonproteobacteria). We show that some of the identified lysogens have co-evolved with their host over geological time scales and that their genes are transcribed in the environment. Functional annotations of lysogeny-related genes suggest involvement in horizontal gene transfer and in host’s protection against toxic metals and antibacterial compounds.